New insights into the Lck-NF-κB signaling pathway - Zhang, Jing; Wu, Yu-Jing; Hu, Xiao-Xi; Wei, Wei (Frontiers in Cell and Developmental Biology, 2023)
Lck is essential for the development, activity, and proliferation of T cells, which may contribute to pathological progression and development of human diseases, such as autoimmune disorders and cancers when functioning aberrantly. Nuclear factor-κB (NF-κB) was initially discovered as a factor bound to the κ light-chain immunoglobulin enhancer in the nuclei of activated B lymphocytes. Activation of the NF-κB pathway controls expression of several genes that are related to cell survival, apoptosis, and inflammation. Abnormal expression of Lck and NF-κB has been found in autoimmune diseases and malignancies, including rheumatoid arthritis, systemic lupus erythematosus, acute T cell lymphocytic leukemia, and human chronic lymphocytic leukemia, etc. NF-κB inhibition is effective against autoimmune diseases and malignancies through blocking inflammatory responses, although it may lead to serious adverse reactions that are unexpected and unwanted. Further investigation of the biochemical and functional interactions between NF-κB and other signaling pathways may be helpful to prevent side-effects. This review aims to clarify the Lck-NF-κB signaling pathway, and provide a basis for identification of new targets and therapeutic approaches against autoimmune diseases and malignancies.